Protocolo para o manejo do paciente com úlcera venosa na atenção primária à saúde no Município de Conselheiro Lafaiete – Minas Gerais - Nascimento Filho, Hélio Martins do [UNIFESP] (2019)
Introduction: Venous ulcers can represent up to 70% of chronic lower limb wounds. The use of clinical care protocols are capable of enhancing healing. Objectives: To develop and validate Protocol for the management of venous ulcer patients in Primary Health Care in the city of Conselheiro Lafaiete - MG. Method: Descriptive and exploratory study approved by the Research Ethics Committee of the Federal University of São Paulo / CAAE: 92538918.3.0000.5505 / Zip Code: 0759.0131.06 / 2018. The analysis of the epidemiological profile, literature review and search in the databases LILACS, BDENF, IBECS, MEDLINE, OVID, CINAHL and SCOPUS between August and November 2018 were carried out. Delphi was attended by nurses and physicians who had experience in assisting venous ulcer patients. For statistical analysis we used the Content Validity Index. Results: The protocol was elaborated based on the literature and with the characteristics of the Health Units where it will be implemented. The global content validity index was 1.0. It consists of 56 pages, illustrations and is divided into: Introduction, Objective, Health Team Assignments, Operationalization, Venous Ulcer Considerations, Patient Assessment, Treatment, Care Guidance, and Topical Therapy Considerations. Conclusion: The protocol for the management of venous ulcer patients in Primary Health Care was developed and validated in the city of Conselheiro Lafaiete - MG.